2020
DOI: 10.1093/femsec/fiaa205
|View full text |Cite
|
Sign up to set email alerts
|

Effects of simulated drought on biological soil quality, microbial diversity and yields under long-term conventional and organic agriculture

Abstract: Drought and agricultural management influence soil microorganisms with unknown consequences for the functioning of agroecosystems. We simulated drought periods in organic (biodynamic) and conventional wheat fields and monitored effects on soil water content, microorganisms and crops. Above the wilting point, water content and microbial respiration were higher under biodynamic than conventional farming. Highest bacterial and fungal abundance were found in biodynamically managed soils, and distinct microbial com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 86 publications
(83 reference statements)
5
31
1
Order By: Relevance
“…On T1, we further found reduced Ndfs values under drought conditions in the ConMin system but not in the BioDyn system. In a previous drought experiment at the same site and with the same crop, we found up to three times more arbuscular mycorrhizal fungi (AMF) under drought conditions in the biodynamic compared to the conventional farming system [38]. Assuming that similar AMF abundance patterns also characterized the current experiment, we can speculate that plants in the BioDyn system under drought conditions profited from the fungal-mediated transport of N [39].…”
Section: Effects Of Drought and Farming System On Plant And N-related Processessupporting
confidence: 72%
“…On T1, we further found reduced Ndfs values under drought conditions in the ConMin system but not in the BioDyn system. In a previous drought experiment at the same site and with the same crop, we found up to three times more arbuscular mycorrhizal fungi (AMF) under drought conditions in the biodynamic compared to the conventional farming system [38]. Assuming that similar AMF abundance patterns also characterized the current experiment, we can speculate that plants in the BioDyn system under drought conditions profited from the fungal-mediated transport of N [39].…”
Section: Effects Of Drought and Farming System On Plant And N-related Processessupporting
confidence: 72%
“…Additionally, plant properties (root dry weight, wheat biomass, wheat height, grain yield, weed cover, and concentrations of nitrogen and carbon of shoots and roots) and microbial activity (soil respiration) were measured (all at T2, except grain yield at T3). Further, data on the microbial community composition were obtained by measuring phospholipid fatty acids (PLFAs) and neutral lipid fatty acids (NLFAs) from soil samples at T2 (Kundel et al, 2020).…”
Section: Soil and Plant Propertiesmentioning
confidence: 99%
“…Although crop breeding has large potential to enhance agricultural productivity, it should certainly not be seen as the only option. Adapted crop management is discussed as an additional solution to mitigate yield loss under drought, either by sustaining plant growth or by enhancing soil water availability (Cochard, 2002;Bot & Benites, 2005;Kundel et al, 2020). Therefore, there is a growing interest in organic farming and conservation tillage (i.e., no tillage or reduced tillage), as these management practices have been shown to be beneficial to soil health and water holding capacity, ecosystem stability, as well as environmental sustainability (e.g., Seitz et al, 2019;Teasdale et al, 2007;Hobbs et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…As global agriculture has already been considerably compromised by and become increasingly particularly under drought (Bot & Benites, 2005;Gomiero et al, 2011;Choudhary et al, 2016). For instance, organic management and conservation tillage can increase soil water holding capacity, therefore providing higher water availability than conventional management and intensive tillage (e.g., Colombi et al, 2019;Kundel et al, 2020). In this study, the systems with conservation tillage (C-NT and O-RT) indeed showed slightly higher SWC than systems with intensive tillage (C-IT and O-IT) at 40 cm (Fig.…”
mentioning
confidence: 99%